Treatment Readiness, Attitudes Toward, and Experiences with Methadone and Buprenorphine Maintenance Therapy Among People Who Inject Drugs in Malaysia - Vijay, A.; Bazazi, A.R.; Yee, I.; Kamarulzaman, A.; Altice, F.L. (Elsevier, 2015)
Background: Little is known about attitudes toward and experiences with opioid maintenance therapy (OMT) among people who inject drugs in Malaysia, a country where people who inject drugs comprise 1.3% of the adult population. Methods: In 2010, 460 people who inject drugs in Greater Kuala Lumpur, Malaysia were surveyed to evaluate attitudes toward and experiences with OMT and treatment readiness. Attitudes towards OMT with both methadone and buprenorphine were assessed using an opinions scale. Multivariable linear regression was used to assess correlates of treatment readiness, measured with the 19-item Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES). Results: All 460 participants used opioids and nearly all (99.1%) met criteria for opioid dependence. Few had had previous experience with methadone (9.3%) or buprenorphine (12.6%) maintenance therapy, yet many had used methadone (55.2%) or buprenorphine (51.7%) outside of treatment settings. Fifteen percent had injected buprenorphine in the past month, and of the few that were currently receiving buprenorphine maintenance therapy, almost all were injecting it. The majority of subjects exhibited a moderate level of treatment readiness and a preference for methadone over buprenorphine. Those with low treatment readiness scores were more likely to have previous experience with compulsory drug detention centers (p. <. 0.01), needle/syringe exchange programs (p. <. 0.005), or be of Indian ethnicity (p. <. 0.001). Past use of methadone (p. <. 0.01), older age (p. <. 0.001), higher stress symptom severity (p. <. 0.001), and sharing of needles or syringes (p. <. 0.05) were associated with higher treatment readiness scores. Conclusion: There are suboptimal levels of OMT experience among people who inject drugs that may be improved by addressing factors that influence patient attitudes. Those individuals with moderate treatment readiness may be targeted by brief motivational and cognitive interventions in primary care, prisons or OMT clinics aimed at improving entry into and retention in treatment.